Two‐Way Gateway Designs to Allow Free Movement Between Safe Havens for Bettongs: A Captive Trial - Xin Lei Pan; Julia M. Hoy; Megan J. Brady; Adrian D. Manning; Megan C. Edwards (Ecology and Evolution)
ABSTRACT Introduced predators in Australia are one of the major causes of native fauna species decline, with attempts to address this decline including predator control, wildlife reintroductions and predator‐proof conservation fencing. The efficacy of conservation fencing means this tool is increasingly used to counteract species decline; however, there is growing awareness that fences can also contribute to issues such as overpopulation, prey naivety and restrictions to natural dispersal and genetic diversity. This research aimed to investigate the potential for two‐way gateways within fences to help address these limitations, allowing movement of native wildlife while reducing introduced predators. Rufous bettongs (Aepyprymnus rufescens) were used for this research as a model species representing ‘critical weight range’ mammals. Seven individually housed captive rufous bettongs were used to investigate interactions with and preference for five gateway designs. Using adaptive methodology, individual rufous bettongs were presented with four of the five gateways and their responses were analysed. The seven rufous bettongs at different life stages and sizes were all able to use all five gateway designs presented to them and showed a preference for designs made from PVC pipe. Gateway positions also significantly influenced the frequency of interactions with the gateways, with bettongs showing a preference for gateways along the edge of the fence rather than the middle. The results from this study are an important step in the development of innovative strategies for safe haven design and improving the performance of semi‐permeable fenced areas for conservation of species impacted by introduced predators. Further testing of these gateways in situ will contribute to the field of ‘coexistence conservation’ – the long‐term, iterative and adaptive process to enable the coexistence of threatened species and native or introduced predators.